PRIVATE DEMANDS, TINGKAT PENGGUNAAN INTERNET PRIBADI DI TEMPAT KERJA DAN KINERJA - Nina Romapurnamasari (Magister Manajemen Fakultas Ekonomi dan Bisnis UNS, 2015)
This study aimed to examine the effect of private demandsto personal Internet use at workplace with four moderating variables and its influence on employee performance.The population in this study were 50 employees at the Muhammadiyah University of Surakarta and 60 employees Perum Perhutani Wilayah Surakarta. Simple random sampling is used to select the sample and the sample obtained 107 employees. This study uses Moderated Regression Analysis and Simple Regression Analysis.The results showed that the private demands affect the use of personal Internet at workplace and influence at the workplace also successfully predicted as a moderating variable in the relationship. In addition it was also found that the use of personal Internet at workplace affect employee performance. But for the other results, border strength, identification with and perceive the job of supervisor support for border crossing failure predicted as a moderating variable on the relationship of private demands on the use of personal Internet at workplace.